Rumen microbial community and milk quality in Holstein lactating cows fed olive oil pomace as part in a sustainable feeding strategy - F. Scicutella; M.A. Cucu; F. Mannelli; R. Pastorelli; M. Daghio; P. Paoli; L. Pazzagli; L. Turini; A. Mantino; S. Luti; M. Genovese; C. Viti; et al. (Animal, 2023)
The use of alternative feed ingredients from the Agro-industry could be an efficient tool to improve the sustainability of dairy cow production. Since the richness in polyphenols, olive oil pomace (OOP), produced during olive oil milling, seems a promising by-product to ameliorate milk’s nutritional value. The aim of this study was to test the use of OOP produced by means of a new technology (biphasic with stone deprivation) in dairy cow feeding strategy to evaluate the effect on animal performances, rumen microbiota, biohydrogenation processes and milk quality by a multidisciplinary approach. Forty multiparous Italian-Friesian dairy cows, at middle lactation, were randomly allotted into two homogenous groups and fed respectively a commercial diet (CON) and the experimental diet (OOPD) obtained by adding OOP to CON as partial replacement of maize silage. The two diets were formulated to be isoproteic and isoenergetic. The same diets were tested also in an in vitro trial aimed to evaluate their rumen degradability (% DEG). The dietary supplementation with OOP did not affect DM intake, rumen % DEG and milk production. The milk’s nutritional quality was improved by increasing several important functional fatty acids (FAs; i.e., linoleic acid, conjugated linoleic acid, oleic acid, vaccenic acid). This finding was related to a decrease in rumen liquor biohydrogenation rate of unsaturated FAs. The stochiometric relation between volatile FA production in the rumen and methanogenesis suggested that OOP lowers the methane potential production (CON = 0.050 mol/L vs OOPD = 0.024 mol/L, SEM = 0.005, P = 0.0011). Rumen microbiota and fungi community did not be strongly altered by OOP dietary inclusion because few bacteria were affected at the genus level only. Particularly, Acetobacter, Prevotellaceae_UCG-004, Prevotellaceae_UCG-001, Eubacterium coprostanoligenes, Lachnospira, Acetitomaulatum, Lachnospiraceae_NK3A20 group were more abundant with OOPD condition (P < 0.05). Data reported in this study confirm that the use of OOP in dairy cow feeding can be an interesting strategy to improve milk nutritional quality increasing functional FA content without compromising the rumen degradability of the diet or causing strong perturbation of rumen ecosystem and maintaining animal performances.